Peran Perusahaan Asuransi Syariah Unit Link dalam Perkembangan Ekonomi Digital di Indonesia - Santi, Mei (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2018)
AbstractThe role of unit link sharia insurance companies in the development of digital economics in Indonesia can be described as follows: in providing information related to company profiles, products and also several other provisions, it can be easily accessed using the internet on their respective websites. in Indonesia under the supervision of the FSA both through mobile and laptop media. For information regarding the customer policy, it is also provided convenience with the application on the smartphone about the policies owned by the customer provided by the company. When a customer has a complaint or question about the product purchased can be via a special email for customers in addition to talking via phone via the call center that has also been provided by the company.  Keywords: digital, economic, company, sharia insurance